PEER ASSESSMENT IN ORAL DESCRIPTIVE TEXT TO THE TENTH GRADERS OF SMAN 1 KRIAN - NUR KUMALASARI, INDAH (RETAIN : Journal of Research in English Language Teaching, 2013)
Berbicara adalah bagian penting dari pembelajaran bahasa. Dalam menilai kegiatan berbicara, beberapa alternatif juga tersedia untuk para guru untuk mendapatkan data lebih lanjut tentang hasil siswa. Salah satunya adalah penilaian teman sebaya. Desain penelitian ini adalah deskriptif kualitatif. Instrument yang digunakan adalah catatan lapangan dan ceklist pengamatan. Peneliti juga mendapatkan data dengan mewawancara siswa dan guru. Penelitian ini dilaksanakan dalam tiga pengamatan di SMA Negeri 1 Krian untuk mengetahui implementasi penilaian teman sebaya pada penampilan bahasa Inggris teks deskriptif siswa kelas 10. Hasil pengamatan menunjukkan bahwa penilaian teman sebaya terbukti membantu dan berpengaruh terhadap siswa. Penilaian teman sebaya membuat siswa mendapatkan informasi tentang hal hal yang harus mereka perbaiki di penampilan di masa depan dan membantu memberi timbal balik yang positif untuk siswa. Keyword: penilaian, berbicara, deskriptif Abstract Speaking is an essential part of learning language. In assessing speaking, some alternatives are also available for the teachers to gain more data about the students’ outcome. One of them is peer assessment. The design of this study was descriptive qualitative research. The instruments were field notes and observation checklist. The researcher also gained the data from interviewing the students and the teacher. This research was conducted in three observations in SMA Negeri 1 Krian to find out the implementation of peer assessment in English oral performance of descriptive text for the tenth graders of the school. The result of the observations shows that peer assessment is proven to be helpful and influential toward the students. It lets the students gain more information about some points to be improved in their future performance. It is helpful and gives positive feedback for the students. Keyword: assessment, speaking, descriptive